2018
DOI: 10.1016/j.cropro.2018.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Economic feasibility of an augmentative biological control industry in Niger

Abstract: Farmers in Niger are vulnerable to high millet yield losses due to the millet head miner, Heliocheilus albipunctella De Joannis (Lepidoptera: Noctuidae), for which pest control options are limited. Researchers have developed a procedure to multiply and spread an augmentative biological control agent Habrobracon hebetor Say (Hymenoptera: Braconidae) which is effective in limiting millet yield losses due to the pest. This study assesses the economic viability of small businesses to produce and sell biological co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…This will reduce the current numbers by 20%. Given the current price of $3.34 per bag (Guerci et al 2018) a saving of $10 is expected per each release. Further investigations will be needed to confirm the effectiveness of the 800 parasitoids dose under higher MHM infestation for consistency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This will reduce the current numbers by 20%. Given the current price of $3.34 per bag (Guerci et al 2018) a saving of $10 is expected per each release. Further investigations will be needed to confirm the effectiveness of the 800 parasitoids dose under higher MHM infestation for consistency.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the critical need for timely release of agents for effective augmentative biological control programs (van Lenteren 2012;El-Heneidy et al 1991;Neuville et al 2016). This information is needed since the technology is being transferred to farmers in Niger (Amadou et al 2017;Guerci et al 2018). Farmers need to know the exact number of parasitoids to be released, and the correct time of release, either at a specific crop developmental stage or at the first appearance of the pest.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of reducing pest-induced hunger in Africa was vividly illustrated to me on a recent trip with two students to Niger. Scientists there were working on a biocontrol solution for millet head miner, a pest that reduced production of the most important food crop in the country by more than 30% per year (Guerci et al 2018). After meeting with farmers in a rural village to discuss the pest problem, the scientists, the students, and I stopped along the road to eat boxed lunches under a tree.…”
Section: Integrated Pest Managementmentioning
confidence: 99%
“…Biological control with release of the parasitoid wasp Habrobracon (= Bracon) hebetor Say (Hymenoptera: Braconidae) resulted in parasitism of 80% of the MHM larvae and resulted in an increase of 30% grain yield (Payne et al 2011;Ba et al 2013;Baoua et al 2014). Even though proven effective, means for making biocontrol agents available at large scale is still under development (Guerci et al 2018;Kabore et al 2019). Therefore, host plant resistance (HPR) can be exploited to complement the ongoing biological control efforts as an integrated pest management strategy for MHM.…”
Section: Introductionmentioning
confidence: 99%